2009
DOI: 10.2109/jcersj2.117.797
|View full text |Cite
|
Sign up to set email alerts
|

Study of the morphotropic phase boundary in the lead-free Na<sub>1/2</sub>Bi<sub>1/2</sub>TiO<sub>3</sub>-BaTiO<sub>3</sub> system by Raman spectroscopy

Abstract: Lead-free piezoelectric (100-x)Na1/2Bi1/2TiO3-xBaTiO3 solid solution ceramics are investigated by Raman spectroscopy and Xray diffraction over a composition range of 0 ≤ x ≤ 10. Distinct changes in the Raman spectra and X-ray diffraction patterns were discussed in the light of a rhombohedral to tetragonal phase transition. The dominant bands in the Raman spectra were analyzed by observing the changes in their respective peak positions, widths and intensities as the composition increased. Based on these results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 18 publications
11
48
0
Order By: Relevance
“…We do not assign here the normal-mode vibrations that are responsible for the Raman lines, but note that these are already discussed in the literature. 33 Simple inspection of the spectra shows clearly altered patterns between 5 and 6% BT, signalled here by (1) third pseudocubic phase; we will return to this point in connection with spectra from poled samples. Note that these spectra bear a very strong resemblance to those reported by Rout et al, 33 which confirmed the existence of the phase boundary near 6% marked in Fig.…”
Section: Methodsmentioning
confidence: 73%
“…We do not assign here the normal-mode vibrations that are responsible for the Raman lines, but note that these are already discussed in the literature. 33 Simple inspection of the spectra shows clearly altered patterns between 5 and 6% BT, signalled here by (1) third pseudocubic phase; we will return to this point in connection with spectra from poled samples. Note that these spectra bear a very strong resemblance to those reported by Rout et al, 33 which confirmed the existence of the phase boundary near 6% marked in Fig.…”
Section: Methodsmentioning
confidence: 73%
“…A significant controversy related to the MPB region for the BNBT composition is found in the literature (11)(12)(13)(14). Recent works, based on the variation of the electrical properties and in-situ synchrotron diffraction analysis, have positioned the MPB region for BNBT bulk ceramics for x values between 0.050 and 0.110, where the transition from the space group R3m to the P4mm one occurs (15).…”
Section: Resultsmentioning
confidence: 99%
“…Three strong Raman bands appear in all the crystal plates, in which the shape, positions, intensity and bandwidth of the peaks exhibit great differences on the crystal orientations. The diffused Raman bands centered around 300, 560 ] stretching vibration and "soft mode" mixed by bending and stretching vibrations [5,7,18]. Fine Raman spectroscopy research indicates that the [TiO 6 ] octahedron vibrations are composed of six species of vibration modes [18].…”
Section: 1mentioning
confidence: 99%
“…The infrared-absorption band occurred around 630.6 cm 1 can be assigned to the "stretching" normal vibration of [Na With the demand for sustainable development of environmental protection and human society, development of lead-free piezoelectric materials that can replace hazardous lead-based Pb(Zr x Ti 1x )O 3 (PZT) piezoelectric ceramics has been research hot in piezoelectric application fields [1][2][3]. Among lead-free piezoelectric materials, (1x)(Na 1/2 Bi 1/2 ) TiO 3 -xBaTiO 3 (NBT-BT) solid solutions attract great research attention due to their excellent piezoelectric performance [4,5]. Since piezoelectric materials existence in crystallographically engineered single crystals exhibit more excellent piezoelectric properties, much work has been undertaken on the growth of high-quality and large-size NBT-BT single crystals [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation